2019
DOI: 10.1016/j.devcel.2019.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Lumen Expansion Facilitates Epiblast-Primitive Endoderm Fate Specification during Mouse Blastocyst Formation

Abstract: SummaryEpithelial tissues typically form lumina. In mammalian blastocysts, in which the first embryonic lumen forms, many studies have investigated how the cell lineages are specified through genetics and signaling, whereas potential roles of the fluid lumen have yet to be investigated. We discover that in mouse pre-implantation embryos at the onset of lumen formation, cytoplasmic vesicles are secreted into intercellular space. The segregation of epiblast and primitive endoderm directly follows lumen coalescen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 77 publications
4
71
0
Order By: Relevance
“…A recent study showed that luminal signalling can also influence epiblastprimitive endoderm lineage segregation within the inner cell mass during mouse blastocyst development ( Fig. 2D; Ryan et al, 2019). In this study, it was shown that inhibition of FGF4 in the lumen impairs cell-fate specification and sorting, whereas luminal deposition of FGF4 expedites the segregation process.…”
Section: Biochemical Signallingsupporting
confidence: 54%
See 2 more Smart Citations
“…A recent study showed that luminal signalling can also influence epiblastprimitive endoderm lineage segregation within the inner cell mass during mouse blastocyst development ( Fig. 2D; Ryan et al, 2019). In this study, it was shown that inhibition of FGF4 in the lumen impairs cell-fate specification and sorting, whereas luminal deposition of FGF4 expedites the segregation process.…”
Section: Biochemical Signallingsupporting
confidence: 54%
“…During the initial phase of mouse blastocoel (see Glossary, Box 1) formation, pressurized fluid is injected into intercellular space, possibly through a combination of cytoplasmic vesicle release and fluid inflow from outside the embryo. This causes a separation of the cell membranes and displacement of cell-cell adhesion molecules (Dumortier et al, 2019;Ryan et al, 2019), a process known as hydraulic fracturing. Furthermore, as luminal surface tension is coupled to the hydrostatic pressure of the lumen through the Young-Laplace Law (see Glossary, Box 1), cell contractility can influence the size, coalescence (see Glossary, Box 1) dynamics and the final positioning of lumen within the tissue (Chan et al, 2019;Dumortier et al, 2019).…”
Section: Biomechanical Control Of Luminogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…These ventricle-like lumen formation is a hallmark of healthy developed organoids in early stages [ 69 , 70 ]. Lumens supply Sox2+ cells that differentiate and migrate to support neurogenesis, ventricle expansion, and cortical development [ 68 , [71] , [72] , [73] ]. Thus, lumen properties (size, thickness, and number) may be critical to the organoids' subsequent cortical layer development [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…In human cerebral organoids, the lumen is the source of undifferentiated stem cells, which is critical for cortical development. These stem cells differentiate batch by batch into neurons, migrate to the organoid edge, and form matured layers [ 71 ] . Thus, the success of the following corticogenesis in the organoids depends on the quality of lumen structures and mature neuronal layer.…”
Section: Resultsmentioning
confidence: 99%